Compliance of school food guidelines in primary schools in mexico city - Tijerina Walls, María Virginia; Rojas-Russell, Mario E; Aedo, María de los Ángeles; Pelcastre-Villafuerte, Blanca Estela; Díaz-Bouchain, eorgina (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
Childhood obesity is a major public health issue in Mexico. Schools are important settings to promote healthy eating habits. The aim of this study was to assess the extent of compliance with 2010 and 2014 Mexican school food guidelines in six public primary schools in Mexico City. The instruments for this study included semi-structured interviews (n=17) with principals, food vendors and members of the School Vending Committee, focus groups (n=10) with teachers and with parents, observation of six schools’ environments, questionnaires applied to 325 schoolchildren from 4th, 5th and 6th grades and their parents, and a food analysis of items sold at school vending. Guidelines’ compliance was assessed using all instruments accordingly. It was low in every dimension: 1) Acknowledgment of school food guidelines: None of the participants were familiar with the 2014 guidelines. 2) Healthy environment enhancement: Children lacked free access to safe drinking water. Children had up to five opportunities to eat during school day besides breakfast at home. Most children (67.7%) ate three to four times. 3) Operability of food and beverages sale and consumption: The only training provided to stakeholders was an annual session on hygiene to school food vendors. The majority of food and beverages offered at school vending exceeded energy, sodium, fat and added sugar content as established. Children sold energy-dense foods for school fundraising. Lack of dissemination and acknowledgment of the guidelines, defined roles and policy procedures, as well as training and capacity building for stakeholders impeded school food guidelines’proper implementation. La obesidad infantil es un problema de salud pública en México. La escuela es un lugar importante para promover hábitos saludables. El propósito del estudio fue evaluar el cumplimiento de los lineamientos escolares de alimentos de 2010 y 2014 en seis escuelas primarias públicas de la Ciudad de México. Los instrumentos incluyen entrevistas semi-estructuradas (n=17) con directores, vendedores de alimentos y miembros del Comité del Establecimiento de Consumo Escolar, grupos focales (n=10) con padres y con profesores, observación del entorno escolar, cuestionarios aplicados a 325 niños de 4º, 5º y 6º grado y a sus padres, y un análisis de los alimentos ofrecidos en la venta escolar. El cumplimiento de los lineamientos fue bajo en cada dimensión: 1) Conocimiento de los lineamientos: Ninguno de los participantes conocía los lineamientos de 2014. 2) Promoción de un ambiente saludable: No se tenía acceso libre a agua simple potable. Los niños tenían cinco oportunidades para comer durante la jornada escolar además del desayuno en casa. La mayoría de los niños (67.7%) comía de 3 a 4 veces. 3) Operatividad de la venta y consumo de alimentos y bebidas: La única capacitación fue una sesión anual de higiene a los vendedores. La mayoría de los alimentos y bebidas excedía los límites establecidos de calorías, sodio, grasa y azúcar añadida. Los niños vendían alimentos densos en energía para recaudar fondos. La falta de difusión de las guías, roles y políticas no definidos y una mínima capacitación obstaculizaron la implementación de los lineamientos.